Novel Conditions in Conservation Translocations: A Conservative-Extrapolative Strategic Framework - Hunter-Ayad, James; Jarvie, Scott; Greaves, Glen; Digby, Andrew; Ohlemüller, Ralf; Recio, Mariano R.; Seddon, Philip J. (Frontiers in Conservation Science, 2021)
In response to anthropogenic threats, conservation translocations are increasingly used to combat species’ population and range declines. However, moving animals outside of their current distribution can mean introducing them to novel conditions, even in the case of reintroductions to formerly inhabited areas due to ecosystem changes following extirpation. This exposure to novel conditions introduces uncertainty that can undermine decision making for species conservation. Here we propose two strategies, which we define as conservative and extrapolative, for approaching and managing novelty and the resulting uncertainty in conservation translocations. Conservative strategies are characterised by the avoidance and removal of novel conditions as much as possible, whereas extrapolative strategies are more experimental, allowing exposure to novel conditions and monitoring outcomes to increase understanding of a species’ ecology. As each strategy carries specific risks and opportunities, they will be applicable in different scenarios. Conservative strategies are best used for translocations of highly threatened species for which ensuring post-release survival is a priority. Whereas extrapolative strategies suit species that are in recovery and so can afford some experimental management and species facing novel and emerging threats which require non-traditional translocations, such as assisted colonisations, be considered. We provide examples, applying our framework to two endemic New Zealand species with long histories of translocation management: tuatara (Sphenodon punctatus), a reptile and takahē (Porphyrio hochstetteri), a flightless bird.